1982
DOI: 10.1037/0021-9010.67.5.533
|View full text |Cite
|
Sign up to set email alerts
|

Managing organizational stress: A field experiment.

Abstract: Although the deleterious effects of work-related stress on employee well-being and organizational effectiveness have received wide attention in the literature, few, if any, controlled experiments have been attempted to assess the effects of stress reduction interventions. In the present study, a stress management training program was evaluated in a field experiment with 79 public agency employees who were randomly assigned to treatment (« = 40) and control (n -39) groups.The training program consisted of 16 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 18 publications
1
39
0
2
Order By: Relevance
“…An examination of these 11 studies reveals a rather odd selection of studies of varying methodological rigor and mixed outcomes and whose results do not appear to fully justify the conclusion drawn by Burke. One was an unpublished dissertation (Campbell, 1973), two provided no quantitative data (Falconer and Hornick, 1983;Blake and Mouton, 1984), a fourth was not an evaluation of an intervention (Pierce and Newstom, 1983), and two further studies were individually orientated interventions, not organizational interventions (Culbert and Renshaw, 1972;Ganster et al, 1982). Of the remaining ®ve studies, Quick (1979) reported signi®cant changes in role con¯ict and role ambiguity but not in absence 5 and 8 months after a goal-setting intervention.…”
Section: Examples Of the Evidencementioning
confidence: 98%
See 1 more Smart Citation
“…An examination of these 11 studies reveals a rather odd selection of studies of varying methodological rigor and mixed outcomes and whose results do not appear to fully justify the conclusion drawn by Burke. One was an unpublished dissertation (Campbell, 1973), two provided no quantitative data (Falconer and Hornick, 1983;Blake and Mouton, 1984), a fourth was not an evaluation of an intervention (Pierce and Newstom, 1983), and two further studies were individually orientated interventions, not organizational interventions (Culbert and Renshaw, 1972;Ganster et al, 1982). Of the remaining ®ve studies, Quick (1979) reported signi®cant changes in role con¯ict and role ambiguity but not in absence 5 and 8 months after a goal-setting intervention.…”
Section: Examples Of the Evidencementioning
confidence: 98%
“…At least three explicit reasons are usually oered: ®rst, tackling the presumed causes of stress is seen as more eective than simply trying to deal with the presumed eects of stressÐin other words prevention is better than cure; second, evaluations of individual stress interventions, such as stress management training, have revealed only limited and short-term eectiveness (e.g. Allison, Cooper and Reynolds, 1989;Ganster, Mayes, Sime and Tharp, 1982;Sallis, Trevorrow, Johnson, Hovell and Kaplan, 1987) and hence organizational interventions are likely to be more eective; third, targeting interventions at the individual level is viewed as somehow blaming the victim (e.g. Murphy, 1988).…”
mentioning
confidence: 99%
“…While most other individual-level stress management interventions have been used to change the way employees appraise their current stressors (e.g., Ganster, Mayes, Sime, & Tharp, 2002), reduce the problem stressors (e.g., Searle, 2008) or change the way employees cope with current strain (e.g., Kabat-Zinn, 1990), self-leadership training provides individuals with resources that not only enable them to address current stressors but also prevent future stressors from occurring. Whereas previous research has examined stress management interventions in relation to a specific stressor in this research we examined individuals in a wide range of organizational settings where the range of potential stressors varied naturally.…”
Section: Discussionmentioning
confidence: 99%
“…Research on organizational stress suggests that work-related stress is a critical influence on employee health and well-being (Ganster, Mayes, Sime, & Tharp, 1982;see also, Cooper & Marshall, 1976;Kasl, 1973). In fact, medical research has documented the physical changes that occur to the body in response to stress.…”
Section: Outcomes Linked To Perceived Control Over Timementioning
confidence: 99%